2016
DOI: 10.21511/ppm.14(3-3).2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the critical factors that hinder the growth of incubatees in South Africa

Abstract: In as much as entrepreneurial action fosters job creation and economic growth, entrepreneurs encounter the significant risk of failure, and community bears the brunt. Though business incubators were designed to provide support and hope to ailing businesses, evidence suggests that not all on these programs succeed. Going on the assumption that even businesses on incubation programs do not seem to be immune to failure, this study sought to determine the key factors that hinder the growth of incubatees in South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Additionally, as mentioned by Ardyan (2016, p. 91), SMEs must be able to "monitor competitor's strategy, comprehend external business market trends, and be responsive to the ever-changing market environment conditions" to increase performance. The world has become a global village because of information technology (Lose, Tengeh, Mazirir, & Madinga, 2016). This has posed a significant challenge to development and growth, particularly for SMEs.…”
Section: Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, as mentioned by Ardyan (2016, p. 91), SMEs must be able to "monitor competitor's strategy, comprehend external business market trends, and be responsive to the ever-changing market environment conditions" to increase performance. The world has become a global village because of information technology (Lose, Tengeh, Mazirir, & Madinga, 2016). This has posed a significant challenge to development and growth, particularly for SMEs.…”
Section: Competitionmentioning
confidence: 99%
“…Bourletidis and Triantafyllopoulos (2014) stated that no business can start or continue operating without finance. Lack of raising funding hinders the development of SMEs (Lose, Tengeh, Mazirir & Madinga, 2016). Asoba and Tengeh (2016) concur that the availability of cash flow enables businesses to purchase the necessary machinery, labour, and property to operate a successful business.…”
Section: Effective Management Of Bookkeepingmentioning
confidence: 99%
“…Lack of entrepreneurial skills, access to markets and select main product and design are some of the factors that affect the business development of the tenants in the Business Incubator [41]. Alishiri et.al, found that there are factors that influence the success of a business incubator.…”
Section: Business Incubatormentioning
confidence: 99%
“…This is particularly so, because previous studies have marginally engaged incubators or incubatees along these lines and have confirmed this evidence. For instance, Cullen et al (2014) and Loose et al (2016), focused on incubator service and sustainability and still realised that there were challenges surrounding sustainability of start-ups hence calling for further research studies in the same phenomena.…”
Section: Theoretical Reviewmentioning
confidence: 99%